Key action fields for nearly carbon-neutral districts: stakeholder-specific strategies and practice - Hess, Stefan; Kreulitsch, David; Kalpkirmaz Rizaoglu, Isil; Honold, Anika; Schmid, Mathias; Stobbe, Marc; Nytsch-Geusen, Christoph; Lützkendorf, Thomas (2020)
Abstract: In accordance with the UN Sustainable Development Goals, many countries aim at nearly zero carbon emissions of their building sector by 2050. The research college EnEff.Buildings.2050 is a collaboration of five PhD students and their supervisors to support this goal. In this paper, five key action fields for transformation of urban districts are described, and decisive stakeholders are identified and linked to the action fields. As a case study, the urban district Mierendorff-Island in Berlin is introduced. Three strategies to support transformation are identified: Firstly, new digital planning tools should be applied to assess and improve the energetic performance of new and existing buildings and to illustrate it to decision makers. Secondly, digital processes should be combined throughout the lifecycle of a building by building information modeling (BIM). This can ensure the energetic quality and enable cost-effective construction, servicing and monitoring. Thirdly, start-ups and contractors need support for development of new business models and technical solutions, which can e.g. enable disruptive technologies. Awareness of stakeholders on the transformational state of a district enables them to identify windows of opportunity to spring into action. Framework conditions and support measures determine if they act in favour of the transformation or not